COVID-19-related travel restrictions and mobility rights: A test for international human rights standards and EU citizenship - Jerónimo, Patrícia (2020)
While there is still much that we do not know about COVID-19, it has by now become abundantly clear that, far from being “the great equalizer” or a catalyst for international solidarity, the disease is disproportionately impacting the poor and the most vulnerable, fuelling nationalist and xenophobic sentiments, and prompting a resurgence of borders and mobility restrictions all over the globe. Many States have resorted to emergency measures and/or derogated from their international human rights obligations in order to enjoy more leeway when restricting individual freedoms in their “war” against the pandemic. Mobility rights are among the most impacted by the COVID-19-related measures, with lockdowns, mandatory quarantines and travel bans. The article discusses the extent to which the EU Member States’ use of their international and EU law prerogatives to close their borders on public health grounds can be considered to have breached international human rights standards and hindered EU citizenship.